Pengaruh Waktu Adsorpsi Minyak Jelantah Sebagai Bahan Pembuatan Biodiesel Dengan Tanah Liat Terhadap Kualitas Biodiesel - Ahmadi, Ahmadi; Suyanti, Ika; Tikrahsari, Sri Astuti; Aini, Miftahul (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Population growth and industrial development cause oil fuel consumption increases, so availability will thinning because it cannot be renewed. So to overcome that the government issued Presidential Decree No.10 of 2006 concerning Development of Vegetable Fuels. Biodiesel is one of them renewable alternative energy sources which are processed from vegetable oils with use alcohol and NaOH as catalysts through the transesterification process. Used cooking oil is one source of vegetable oil that can used as raw material for making biodiesel through the process transesterification. But the use of used cooking oil directly without through the adsorption process will affect the quality of the biodiesel produced. The purpose of this study is to determine the effect of adsorption time used cooking oil for the quality of biodiesel produced from used cooking oil. This research aimed to know there is or no effect of odsorption time of cooking oil using the clay towards biodiesel quality. Object of this research used cooking oil which is adsorpted with varieties time of adsorption was 0 hour (Control), 12 hours, 36 hours and 48 hours. Based on the result of research showed that adsorption time has effect towards quality, where high adsorption time was 12 hours. Quality of biodiesel has been suitable with SNI. The quality was dencity 0,860 gr/cm3, water degree 0,035% vol, flame coordinate 170oC and acid number 0,71 mg KOH/g oil % the result of biodiesel 55,29%.